Microsurgical Clip Placement for a Giant Anterior Communicating Artery Aneurysm With Intraluminal Thrombus: 2-Dimensional Operative Video. Issue 3 (8th August 2018) - Riechelmann, Guilherme Salemi; da Costa, Marcos Devanir Silva; Caramanti, Ricardo Lourenço; Goiri, Marcelo Augusto Acosta; Costa, Bruno Lourenço; González-Echeverría, Kléber; Chaddad-Neto, Feres
Abstract: Giant brain aneurysms account for approximately 5% of all intracranial aneurysms. Although treatment modalities can vary widely, none is ideal for every patient. Endovascular treatment is usually preferred, especially when the large size of the aneurysm limits visualization of the brain parenchyma and parent vessels that arise from the aneurysm, making surgical clip placement across the neck a difficult task. However, despite the higher chances of morbidity, microsurgery is an effective treatment modality due to lower recurrence rates. Surgically, a wide neck, calcifications, or atheroma are complicating factors to be considered while planning the best treatment. Thus, with an appropriate case selection, a favorable outcome is feasible in most cases. Here, we present the case of a 27-yr-old female who presented with a severe headache for 7 mo and 3 mo of progressive left temporal vision loss, which was confirmed by visual field perimetry using the Humphrey visual field analyzer. Magnetic resonance angiography and digital subtraction cerebral angiography showed an anterior communicating artery complex inferiorly and medially oriented aneurysm measuring 25.4 × 16.5 mm, with a 3 mm neck. It was fed by the right A1, associated with a hypoplastic left A1, incorporating the proximal right and left A2 segments, with an intraluminal thrombus and causing mass effect on the optic chiasm and hypothalamus. This video demonstrates the microsurgical steps required to perform this operation, through a right orbitozygomatic craniotomy. At a 3-mo follow-up, the patient was neurological intact without complaints. The patient signed the Institutional Consent Form, which allows the use of his/her images and videos for any type of medical publications in conferences and/or scientific articles.